Religious images in the scientific works by Mykhailo Maksymovych - Yeremieiev, Pavlo (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2022)
Purpose. The paper deals with the religious images in the works by Mykhailo Maksymovych, a famous Ukrainian botanist, folklorist, linguist, historian, and the first rector of the University in Kyiv.Methods. The methodological foundation became the approaches of the Cambridge School of intellectual history, theorising in cultural memory and quantitative content analysis with MAXQDA-2022. The study is based on the scholar's published works, memoirs, letters, and unpublished texts, saved in the Institution of Manuscript of Vernadsky National Library of Ukraine (Kyiv).Results. It is shown that the attitude of Mykhailo Maksymovych to the demarcation problem of knowledge and faith was the result of his religiosity combined with Mykhailo Maksymovych’s fascination with Friedrich Schelling’s ideas. The scholar perceived the Bible as a relevant description of human history's “factual” dimension. Mykhailo Maksymovych was a representative of the “philosophy of the heart”, widespread in Ukrainian intellectual life of that period.Conclusions. Mykhailo Maksymovych’s religiosity, combined with the features of Romanticism, caused his views on Ukrainian distinctiveness.